KEPEMIMPINAN KIAI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO TERHADAP TRANSFORMASI PENDIDIKAN ISLAM - Djuwairiyah Djuwairiyah; Asyraf Isyraqi Jamil; Fakhrul Adabi Abd Kadir (LP2M Universitas Ibrahimy, 2024)
This study aims to analyze the role of Kiai leadership in transforming Islamic education at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School. The method used in this study is a qualitative approach with a case study research type. Data were collected through in-depth interviews with Kiai, Islamic boarding school administrators, students, direct observation, and documentation. Data analysis was carried out using thematic analysis techniques to identify the role of Kiai in directing, managing, and transforming the Islamic education system in Islamic boarding schools. The study results indicate that Kiai leadership at the Salafiyah Syafi'iyah Sukorejo Islamic Boarding School significantly influences the renewal of the education curriculum, teaching methods, and the development of Islamic boarding school facilities. Kiai plays a central role in maintaining the Salafi tradition while accommodating educational developments that are more relevant to the needs of the times. This transformation includes integrating moderate Islamic values, strengthening educational competencies, and adapting to technological advances in the learning process. This study concludes that Kiai leadership at Salafi Islamic boarding schools is crucial in maintaining the balance between tradition and modernity in Islamic education.